SCALING PLM SYSTEMS FOR GLOBAL OPERATIONS: A CASE STUDY IN THE AUTOMOTIVE SECTOR - Nishant Kapoor (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article examines the implementation of the PTC Windchill PLM system at AutoTech Solutions Inc., a leading Tier-One automotive supplier, focusing on the challenges and solutions in deploying a global PLM system. The article investigates the transformation of product development capabilities through process standardization, system integration, and user adoption strategies. The implementation demonstrated significant achievements in reducing product development cycles, improving data accuracy, and enhancing cross-functional collaboration. The article highlights best practices in solution design, integration with enterprise systems, and sustainable support models, providing valuable insights for organizations pursuing large-scale PLM implementations. The article offers a comprehensive roadmap for enterprises aiming to scale PLM systems globally while driving innovation and operational excellence.